Alternaria blight disease – A serious problem in theseed production of radish (Raphanus sativus) - R., Gangaraj; E. R., Rashmi; K. B., Ramesh; Singh, Vikas (Indian Horticulture, 2025)
Seed is the ultimate input used for the cultivation of any crop. The production of healthy quality seeds free from pests and diseases is the ultimate goal and a big challenge in the seed production centres. Radish is an edible root vegetable grown mainly in the tropical and subtropical regions of the world. The crop in the field is infected by number of plant pathogens including fungi, bacteria and viruses causing significant economic losses. Among them, Alternaria blight is one of the serious disease affecting yield and quality of seeds. It is observed during all the stages of the crop covering entire plant parts and causing nearly half of seed yield loss varying from year to year. The successful management of the disease depends on the correct identification of the causal organism responsible for causing the disease. Considering this, the article briefs about the identification of the disease based on the symptoms, causal organism, cultural and morphological characteristics of the pathogen, disease cycle, conditions required for the spread of the pathogen and best management practices that can be practiced for the successful control of Alternaria disease of radish in the field.